Interaction of membrane cholesterol with GPCRs: implications in receptor oligomerization - Sengupta, D.; Kumar, G. A.; Chattopadhyay, A. (Receptors, 2017)
G protein-coupled receptors (GPCRs) are the largest family of proteins involved in signal transduction across cell membranes, and represent major drug targets in all clinical areas. Oligomerization of GPCRs and its implications in drug discovery constitute an exciting area in contemporary biology. In this review, we have highlighted the role of membrane cholesterol and the actin cytoskeleton in GPCR oligomerization, using a combined approach of homo-FRET and coarse-grain molecular dynamics simulations. In the process, we have highlighted experimental and computational methods that have been successful in analyzing different facets of GPCR association. Analysis of photobleaching homo-FRET data provided novel information about the presence of receptor oligomers under varying conditions. Molecular dynamics simulations have helped to pinpoint transmembrane helices that are involved in forming the receptor dimer interface, and this appears to be dependent on membrane cholesterol content. This gives rise to the exciting and challenging possibility of age and tissue dependence of drug efficacy. We envision that GPCR oligomerization could be a game changer in future drug discovery.

Lipid composition and salt concentration as regulatory factors of the anion selectivity of VDAC studied by coarse-grained molecular dynamics simulations - Van Liefferinge, F.; Krammer, E. -M.; Sengupta, D.; Prevost, M. (Chemistry and Physics of Lipids, 2019)
The voltage-dependent anion channel (VDAC) is a mitochondrial outer membrane protein whose fundamental function is to facilitate and regulate the flow of metabolites between the cytosol and the mitochondrial inter membrane space. Using coarse-grained molecular dynamics simulations, we investigated the dependence of VDAC selectivity towards small inorganic anions on two factors: the ionic strength and the lipid composition. In agreement with experimental data we found that VDAC becomes less anion selective with increasing salt concentration due to the screening of a few basic residues that point into the pore lumen. The molecular dynamics simulations provide insight into the regulation mechanism of VDAC selectivity by the composition in the lipid membrane and suggest that the ion distribution is differently modulated by POPE compared to the POPC bilayer. This occurs through the more persistent interactions of acidic residues located at both rims of the beta-barrel with head groups of POPE which in turn impact the electrostatic potential and thereby the selectivity of the pore. This mechanism occurs not only in POPE single component membranes but also in a mixed POPE/POPC bilayer by an enrichment of POPE over POPC lipids on the surface of VDAC. Thus we show here that computationally-in-expensive coarse-grained simulations are able to capture, in a semi-quantitative way, essential features of VDAC anion selectivity and could pave the way toward a molecular level understanding of metabolite transport in natural membranes.
Keywords: Coarse-grained molecular; Membrane channel; Protein-lipid interactions; VDAC